2016
DOI: 10.1371/journal.pone.0167465
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Predictors of Non-Adherence to Antiretroviral Therapy among HIV-Positive Individuals in Kenya: Results from the Second Kenya AIDS Indicator Survey, 2012

Abstract: IntroductionUnderstanding the levels and associated factors of non-adherence to antiretroviral therapy (ART) is crucial in designing interventions to improve adherence and health outcomes of ART. We assessed non-adherence to ART among HIV-infected persons reporting ART use in a nationally representative survey in Kenya.MethodsThe Kenya AIDS Indicator Survey 2012 was a population-based, household survey of persons aged 18 months-64 years conducted in 2012–2013. Self-reported information was collected on demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
34
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 35 publications
10
34
1
3
Order By: Relevance
“…Furthermore, in the present study, adolescents (those aged !10 years) were more likely to experience VF compared to younger children, a finding that has also been reported by other studies conducted in Africa (Makadzange et al, 2015). Adolescence is a period of particularly high risk for poor adherence (Mukui et al, 2016;Nachega et al, 2009). Taken together, these emphasize the need for investigating and addressing factors that impede viral suppression among adolescents.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, in the present study, adolescents (those aged !10 years) were more likely to experience VF compared to younger children, a finding that has also been reported by other studies conducted in Africa (Makadzange et al, 2015). Adolescence is a period of particularly high risk for poor adherence (Mukui et al, 2016;Nachega et al, 2009). Taken together, these emphasize the need for investigating and addressing factors that impede viral suppression among adolescents.…”
Section: Discussionsupporting
confidence: 76%
“…The adherence rate among pregnant women varies across different settings (within and across countries) from 35% to 93.5% [ 15 ]. A study reported low adherence levels among pregnant women in rural Kwazulu Natal, South Africa [ 14 ]; however, a high level of adherence (90%) was reported in Kenya [ 16 ]. An adherence level of 73% during pregnancy was reported in Malawi, but dropped to 66% by three month postpartum [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The factors associated with non-adherence also vary contextually. For instance, knowledge was linked to non-adherence in Israel [ 25 ], while younger age, rural residence and substance use were important in Kenya [ 16 ]. In Malawi, lack of emotional and financial support from husband, inadequate counseling and internal migration were the reported reasons for non-adherence to ART [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent populations have been shown in previous studies to be the least adherent to ART. A recent national survey in Kenya found higher levels of suboptimal adherence among persons aged 15–29 [ 20 ]. This is in conformity with data from across sub-Saharan Africa which found that ART adherence by pre-teenagers and teenagers is influenced by disclosure [ 21 , 22 ], socioeconomic status [ 23 ], treatment fatigue [ 24 ], fear of stigmatization by peers [ 25 ], and vigilance by the primary caregivers [ 12 , 13 ].…”
Section: Main Textmentioning
confidence: 99%